Job Satisfaction and Relocation Desire among Pediatric Dentists in Puerto Rico - Arévalo, Oscar; Saman, Daniel M.; Tabares, Miguel; Hernández, Ana; Sanders-Ward, Rebecca (Puerto Rico Health Sciences Journal, 2015)
Objective: To determine the levels of satisfaction, license status, and desire to relocate of pediatric dentists in Puerto Rico. Methods: Pediatric dentists in Puerto Rico were surveyed via telephone interviews. Data were collected through a 34-item questionnaire that explored satisfaction as related to income, continuing education, professional goals, and participation in the Mi Salud program. Frequencies, chi-square analysis, and Fisher’s exact 2-tailed t-test were utilized to determine the relationships between satisfaction and the demographics of the pediatric dentists. Results: Sixty pediatric dentists participated in our survey—77% of the total number of pediatric dentists practicing in Puerto Rico. Overall, 65% of the participating pediatric dentists expressed dissatisfaction. Male pediatric dentists were more dissatisfied than their female colleagues were. Most pediatric dentists participating in Mi Salud expressed dissatisfaction. When asked about whether or not they had considered migrating to the mainland, those who were dissatisfied were more likely to have considered that idea than were those who were satisfied. Overall, 57% of the pediatric dentists comprising our sample had considered relocating to the continental United States. Conclusion: In general, the pediatric dentists who participated in our study expressed dissatisfaction in most areas except when asked about their ability to reach professional goals. Determining the levels of satisfaction of health care providers is important in the maintaining of an adequate workforce. As current levels of dissatisfaction are high, it is important to determine what variables are related to satisfaction so that corrective measures can be taken to ensure that retention rates improve, thereby maintaining an adequate pediatric dental workforce.